Synthetic CB1 Cannabinoids Promote Tunneling Nanotube Communication, Cellular Migration, and Epithelial–Mesenchymal Transition in Pancreatic PANC-1 and Colorectal SW-620 Cancer Cell Lines - David A. Bunsick; Leili Baghaie; Yunfan Li; Abdulrahman M. Yaish; Emilyn B. Aucoin; Elizabeth Skapinker; Rashelle Aldbai; Myron R. Szewczuk (Cells)
Metastasizing cancer cells surreptitiously can adapt to metabolic activity during their invasion. By initiating their communications for invasion, cancer cells can reprogram their cellular activities to initiate their proliferation and migration and uniquely counteract metabolic stress during their progression. During this reprogramming process, cancer cells’ metabolism and other cellular activities are integrated and mutually regulated by tunneling nanotube communications to alter their specific metabolic functional drivers of tumor growth and progression. Here, we investigated the in vitro effects of the synthetic CB1 cannabinoids AM-404, arvanil, and olvanil on human pancreatic PANC-1 and colorectal SW-620 cancer cell lines to understand further cellular behaviors and the potential risks of their use in cancer therapy. For the first time, the synthetic CB1 cannabinoids AM-404, arvanil, and olvanil significantly altered cancer cells in forming missile-like shapes to induce tunneling nanotube (TNT) communications in PANC-1 cells. Oseltamivir phosphate (OP) significantly prevented TNT formation. To assess the key survival pathways critical for pancreatic cancer progression, we used the AlamarBlue assay to determine synthetic CB1 cannabinoids to induce the cell’s metabolic viability drivers to stage migratory intercellular communication. The synthetic CB1 cannabinoids significantly increased cell viability compared to the untreated control for PANC-1 and SW-620 cells, and this response was significantly reduced with the NMBR inhibitor BIM-23127, neuraminidase-1 inhibitor OP, and MMP-9 inhibitor (MMP-9i). CB1 cannabinoids also significantly increased N-cadherin and decreased E-cadherin EMT markers compared to the untreated controls, inducing the process of metastatic phenotype for invasion. BIM-23127, MMP9i, and OP significantly inhibited CB1 agonist-induced NFκB-dependent secretory alkaline phosphatase (SEAP) activity. To confirm this concept, we investigated the migratory invasiveness of PANC-1 and SW-620 cancer cells treated with the synthetic CB1 cannabinoids AM-404, arvanil, and olvanil in a scratch wound assay. CB1 cannabinoids significantly induced the rate of migration and invasiveness of PANC-1 cancer cells, whereas they had minimal effect on the rate of migration of already metastatic SW-620 cancer cells. Interestingly, olvanil-treated SW-620 cells significantly enhanced the migration rate and invasiveness of these cells. The data support the cellular and molecular mechanisms of the synthetic CB1 cannabinoids, orchestrating intercellular conduits to enhance metabolic drivers to stage migratory intercellular communication in pancreatic cancer cells.